A Comparison of Avatar-, Video-, and Robot-Mediated Interaction on Users’ Trust in Expertise - Pan, Ye; Steed, Anthony (Frontiers in Robotics and AI, 2016)
Communication technologies are becoming increasingly diverse in form and functionality. A central concern is the ability to detect whether others are trustworthy. Judgments of trustworthiness rely, in part, on assessments of non-verbal cues, which are affected by media representations. In this research, we compared trust formation on three media representations. We presented 24 participants with advisors represented by two of the three alternate formats: video, avatar, or robot. Unknown to the participants, one was an expert, and the other was a non-expert. We observed participants’ advice-seeking behavior under risk as an indicator of their trust in the advisor. We found that most participants preferred seeking advice from the expert, but we also found a tendency for seeking robot or video advice. Avatar advice, in contrast, was more rarely sought. Users’ self-reports support these findings. These results suggest that when users make trust assessments, the physical presence of the robot representation might compensate for the lack of identity cues.